2020
DOI: 10.1002/joc.6852
|View full text |Cite
|
Sign up to set email alerts
|

Examining trends in multiple parameters of seasonally‐relative extreme temperature and dew point events across North America

Abstract: Concurrent with the background rise in global mean temperatures, changes in extreme events are also becoming evident, and are arguably more impactful on society. This research examines trends in three components of seasonallyrelative extreme temperature and humidity events in North America that directly influence human thermal comfort: event frequency, duration, and areal extent. Results indicate that for the majority of the study domain, changes in these events are in the expected direction with changes in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This metric provides insights into the vertical structure of the atmosphere, essential for understanding the overall atmospheric dynamics. Hence while prior studies have documented that global temperature is rising and there are a wide variety of associated indicators of this change, along with potential impacts [16][17][18][19], this study applied ERA5 reanalysis data to examine how global atmospheric layer thickness has changed since 1940.…”
Section: Discussionmentioning
confidence: 99%
“…This metric provides insights into the vertical structure of the atmosphere, essential for understanding the overall atmospheric dynamics. Hence while prior studies have documented that global temperature is rising and there are a wide variety of associated indicators of this change, along with potential impacts [16][17][18][19], this study applied ERA5 reanalysis data to examine how global atmospheric layer thickness has changed since 1940.…”
Section: Discussionmentioning
confidence: 99%
“…While no validation on station-based observations was undertaken specifically for the research described herein, prior research has shown reanalysis temperature data to associate well with observed stationbased data. For example, Lee et al (2021) found that temperature trends in the North American Regional Reanalysisan older-generation reanalysis than ERA5were only significantly different in $2% of locations examined. And, Sheridan et al (2020) found that extreme temperature days from ERA-5 data matched observations 80% of the time over the United States and Canadawith some areas exhibiting >98% accuracybetter than any of the other reanalyses examined.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lee et al . (2021) found that temperature trends in the North American Regional Reanalysis – an older‐generation reanalysis than ERA5 – were only significantly different in ~2% of locations examined. And, Sheridan et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge regarding different aspects of ETEs and any changes or variability is beneficial for many sectors, including health and the environment. For example, a comprehensive analysis and understanding of the temporal behaviors of temperature extremes is a critical component in the development of effective early warning systems [ 29 ], planning for resilient public health systems [ 30 ], and strategies for ETE mitigation and adaptation [ 21 ]. This study aims to update the knowledge on ETEs in Arabia using an extreme temperature seasonal definition that considers both spatial and temporal differences.…”
Section: Introductionmentioning
confidence: 99%